2020
DOI: 10.1002/cam4.2981
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in Hodgkin lymphoma patients: A Danish nationwide cohort study of 945 patients

Abstract: Cancer‐related psychological distress may lead to depression and anxiety among survivors. The vast majority of patients with Hodgkin lymphoma (HL) become long‐term survivors, but the risk of mental health problems after HL is not well‐characterized. Using national population‐based registries, we investigated the cumulative incidence of psychotropic drug (antidepressants, antipsychotics, and anxiolytics) use (proxies for depression and anxiety) in HL patients as well as if an increased risk would normalize over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 49 publications
(102 reference statements)
0
25
0
1
Order By: Relevance
“…Cancers with better prognoses (eg, thyroid cancer) generally had lower risks of MDD, although patients with breast cancer, which has a 5-year relative survival rate 25 and conditional 5-year relative survival rate 26 22 head and neck, 27 lung, 24 colorectal, 28,29 thyroid, 30 gastric, 31 cervical, 32 and breast cancer, 33 as well as Hodgkin lymphoma. 34 The size of our study allowed us to determine the risk of MDD for many more types of cancer than previously studied. However, the relatively low numbers of patients with some rarer types of cancer made it difficult to accurately determine HRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancers with better prognoses (eg, thyroid cancer) generally had lower risks of MDD, although patients with breast cancer, which has a 5-year relative survival rate 25 and conditional 5-year relative survival rate 26 22 head and neck, 27 lung, 24 colorectal, 28,29 thyroid, 30 gastric, 31 cervical, 32 and breast cancer, 33 as well as Hodgkin lymphoma. 34 The size of our study allowed us to determine the risk of MDD for many more types of cancer than previously studied. However, the relatively low numbers of patients with some rarer types of cancer made it difficult to accurately determine HRs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, subgroup analysis of cancer patients suggested that those who received inpatient chemotherapy within 2 months of diagnosis, reflecting more serious cancer at diagnosis, had a higher risk of MDD. Previous matched cohort studies have reported increased risk of depression in patients with uterine, 22 head and neck, 27 lung, 24 colorectal, 28,29 thyroid, 30 gastric, 31 cervical, 32 and breast cancer, 33 as well as Hodgkin lymphoma 34 . The size of our study allowed us to determine the risk of MDD for many more types of cancer than previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…A brief questionnaire was designed and checked for clarity with a group of psychiatric and gynecological female patients before the start of the main study. The questionnaire was used to assess the self-reported lifetime history of psychiatric disorders [26,42] and current use of psychotropic medications [29,43]. Each patient was asked: (1) whether she had ever been treated for any psychiatric disorder in an outpatient or inpatient setting, (2) whether she had ever been under the care of a psychiatrist.…”
Section: Psychiatric History and Current Treatment With Psychotropic Medicationsmentioning
confidence: 99%
“…To address this aim, female patients referred to a tertiary care urogynecological center by their family physicians for further diagnosis and treatment of OAB were screened for a history of psychiatric disorders [26,27] and the type and number of psychotropic medications currently being taken. Notably, psychotropic medications are commonly used as a simple indicator of mental health problems in different populations of patients [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…During this period, many patients will be anxious about a relapse, and they will be constantly reminded of the insidious nature of cancer when they are screened for asymptomatic relapse during follow‐up visit 1 . Even in diseases with a very low risk of relapse, such as Hodgkin lymphoma, survivors have an increased use of anxiolytics and antidepressants over the background population 2 . In non‐Hodgkin lymphoma (NHL), including follicular lymphoma (FL), treatment decisions are based on national or international guidelines like those proposed by the European Society for Medical Oncology or the National Comprehensive Cancer Network, in which results of key evidence are synthesized into recommendations 3,4 .…”
mentioning
confidence: 99%